IMPLEMENTASI DESIGN THINKING DALAM PENGEMBANGAN BISNIS UMKM MELALUI PLATFORM INSTAGRAM: STUDI KASUS DAPUR QUEENSHA - Fathurahman, Dennis; Maharani, Safira; Hodizah, Siti; Mazia, Lia (LPPM Universitas Nusa Mandiri, 2024)
The development of information technology enables UMKM to reach a wider market through digital marketing, allowing them to attract more customers. This study discusses the implementation of Design Thinking in business development for UMKM, with a case study on Dapur Queensha, a frozen food business. The aim of this research is to enhance the understanding of Design Thinking implementation in UMKM business development using the Instagram platform. This research adopts a descriptive qualitative approach, where data is collected through observation and interviews. The analysis results indicate that Dapur Queensha is striving to promote its products through social media platforms, especially Instagram. The adopted marketing strategy involves leveraging Instagram to market their frozen food products. The proposed solution includes creating attractive and consistent feed designs to post on Instagram and redesigning the existing logo to make it more appealing and simple. Positive feedback from consumers and Instagram users indicates that the design changes have had a positive impact. Additionally, the decision to use Instagram as a marketing tool has proven effective, given its popularity and ability to reach a broad audience.